Immobilization after pediatric supracondylar humerus fracture surgery: Cast or splint - ŞİRİN, EVRİM; POLAT, MURAT; ŞAHBAT, YAVUZ; EROL, BÜLENT; AKGÜLLE, AHMET HAMDİ (My University, 2022)
Objective: While surgical treatment is the most accepted treatment method for displaced supracondylar humerus fractures in children, there is little data about immobilization method after surgery. The aim of the study is to determine whether there is any difference in preventing loss of reduction between long-arm cast and long-arm splint following pediatric supracondylar humerus fracture surgery. Patients and Methods: We conducted a retrospective analysis of pediatric patients with supracondylar humerus fractures treated operatively between 2012 and 2019 at a university hospital. According to Skaggs criteria, early postoperative and 3rd-week follow-up X-rays were evaluated for the loss of reduction (LOR). Postoperative immobilization method; splint or cast was compared in the context of LOR. Results: Cast immobilization was found to be superior in preventing LOR in the first three weeks postoperatively (p˂0.05). There was no significant difference for other factors like fracture configuration, patient age and surgical technique. Conclusion: Cast immobilization is superior to splint immobilization in preventing radiologic LOR after pediatric supracondylar humerus fracture surgery however, clinical relevance of this conclusion is yet to be proved.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Supracondylar humerus fracture; Postoperative immobilization; Loss of reduction; ENTRY PIN FIXATION; CHILDREN; REDUCTION; MANAGEMENT; Supracondylar humerus fracture; Postoperative immobilization; Loss of reduction